In vitro and in vivo activities of Q-35, a new fluoroquinolone, against Mycoplasma pneumoniae. - Gohara, Y (1993)
The in vitro potency and in vivo efficacy of Q-35, a new fluoroquinolone, against Mycoplasma pneumoniae were investigated by pharmacokinetic studies with M. pneumoniae-infected hamsters. By using fluoroquinolones, macrolides, and tetracyclines as references, Q-35 was found to possess the greatest mycoplasmacidal activity. The MIC for 90% of strains tested (MIC90) and the MIC50 were 0.78 and 0.39 microgram/ml, respectively, and the MBC for 90% of strains tested (MBC90) and the MBC50 were 3.13 and 0.78 microgram/ml, respectively. The MBC50-to-MIC50 ratio for Q-35 was 2. Furthermore, only Q-35 continued to be effective against 19 strains of erythromycin-resistant mutants of M. pneumoniae. The efficacies of fluoroquinolones against M. pneumoniae were also investigated by using an experimental hamster pneumonia model to measure the CFU of M. pneumoniae in the lungs. Q-35 and ofloxacin were efficacious following oral administration of 200 mg/kg/day for 5 days, initiated 24 h after infection, while ciprofloxacin was not active. Continuous administration of Q-35 for 10 days significantly reduced numbers of viable M. pneumoniae in the lungs. These results suggest that both Q-35 and ofloxacin are effective in the early phase of infection and, moreover, that Q-35 is also effective in the middle stage of infection, when progressive lung alterations and continuous increases in mycoplasmal growth occur. Peak levels of Q-35 in sera and lungs after oral administration were higher than those of ciprofloxacin but lower than those of ofloxacin. On the basis of these results, Q-35 appears to be a promising antimicrobial agent in chemotherapy of mycoplasmal infection.